Wyłączenie od zeznawania i prawo odmowy zeznań w rzymskim procesie karnym - Nowicka, Dobromiła (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The author of article examines the scope of the exemption from testifying for the prosecution and the right to refuse to testify in the Roman criminal procedure before quaestiones. She focuses mainly of Callistratus’ and Ulpian’s accounts of lex Iulia de vi and Paulus’ account of lex Iulia iudiciorum publicorum. This is because there are doubts, especially with regard to the nature of rights or exemptions applying to testimonies concerning relations based on close kinship (parents-children) or patronage as well as marriage.
Keywords: zeznania świadków; prawo do odmowy składania zeznań; dowody